Textbooks on the international relations theory: What they talk about, what they keep silent about, and what to do about it - N. V. Yudin (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
Theory represents the highest form of scientific knowledge in any discipline, a sort of certificate of maturity of the latter, and, at the same time, the key to its systematic teaching and understanding. From this point of view, international studies show a somewhat paradoxical picture. On the one hand, at the moment there is no shortage of either theoretical studies of international political issues or textbooks on the theory of international relations. On the other hand, their common leitmotif remains the idea that international studies either have not yet acquired a full-f ledged theory, or, due to their inherent complexity, dynamism and inconsistency are not subject to systematic generalization in principle. As a result, teaching of the IR theory turns out to be equally inconvenient for the lecturers, if they want to not just bombard students with terms and personalities, but teach them to effectively use different concepts and approaches, and for students. The author argues that these difficulties stem not only from the objective complexity of international processes and problems, but also from the subjective theoretical, methodological and philosophical specifics of the textbooks on the IR theory. To substantiate this claim this paper examines a selection of modern Russian and foreign textbooks on IR theory. The first section summarizes their key advantages, which include, first of all, the fact that they all successfully perform an educational function, introducing the reader to the key approaches, schools and theories that form the ‘body’ of modern IR theory. In this regard, one can easily find both textbooks specially designed for an unprepared audience which provide an introduction to the discipline, and publications containing an in-depth analysis of the driving forces and internal logic of the IR theory development. At the same time, as shown in the second section, all modern textbooks on IR theory share a number of common short-comings, which can be divided into methodological and philosophical ones. The former include not sufficiently substantiated logic of presentation, the lack of clear criteria for structuring the material and explicitly formulated principles for selecting approaches to be considered. The latter imply reliance on extremely shaky philosophical assumptions, which, consciously or not, reproduce post-modernist views on the problems of ontology and epistemology of international relations and international studies. And it is in a critical revision of these basic philosophical principles where, according to the author, lies the key to addressing the problems in both teaching the IR theory and formulating the theory of international relations in the strict sense.